Discovering Digital Signage System Opportunities as Crowd Attractor in Public Spaces: A Study in Charge Gratis Service - Fathoni, Ahmad Faisal Choiril Anam (Humaniora, 2016)
Article presented a research about the "Charge Gratis" service that included digital signage, along with free charging device as the crowd attractors in the public space. The main focus of this research was about media display embedded in the uniform of a sales promotion person who displays ads from the advertiser using the qualitative method, through the interview with some expert sources many fields. Article described several possibilities that can be worked in the use of digital signage so that it can be used as a reference in maximizing digital signage in public spaces. It finds that Digital signage is not just functioned as like any other media, but also the awaken interaction and also enhance shopping experiences. The expert sources divide this media display functions into three categories, which is a media information, media entertainment, and media education.